Рассказы о Петре Великом - Новаковский Владимир Иванович ("Мгновения истории", 1992)
Печатается по изд.: СПб.: Тип. "Обществ.польза",1896 Экземпляры: ф.3 (20240422) / Инвентарный номер: 63581 / Цена: 10.00 / Авт.знак: Н 72 / ГРНТИ: 03.19 / ББК: 63.3(2)46